Zosteriform Dissemination of Molluscum Contagiosum Infection Diagnosed in an Immunocompetent Girl: A Rare Clinical Presentation - Aya Marashli; Mohammad Adi; Zuheir Al‐shehabi; Lina Al‐Soufi (Clinical Case Reports)
ABSTRACT Molluscum contagiosum (MC) is a benign, self‐limiting infectious lesion that primarily affects children and young adults, especially those with immunodeficiency. MC is caused by a poxvirus from the Molluscipoxvirus genus of the Poxviridae family. Diagnosis is mainly clinical, with lesions presenting as dome‐shaped, spherical, solid, flesh‐colored, pearly papules with central umbilication. MC commonly appears on the limbs, face, trunk, and axillary regions. The differential diagnosis includes inflammatory, infectious, and neoplastic causes, varying by age and immunological condition. This case report presents a rare zosteriform distribution of MC infection in an immunocompetent girl, a presentation described only twice in medical literature. The unusual distribution resulted from scratching, a process known as the Koebner phenomenon (pseudo‐koebnerization).